Surveillance of Resistance to New Antibiotics in an Era of Limited Treatment Options - Morel, Chantal M.; de Kraker, Marlieke E. A.; Harbarth, Stephan; , The Enhanced Surveillance Expert Consensus Group (CANSORT-SCI) (Frontiers in Medicine, 2021)
As with any health threat, our ability to respond to the emergence and spread of antimicrobial resistance depends on our ability to understand the scale of the problem; magnitude, geographical spread, and trends over time. This is especially true for resistance emergence to newer antibiotics coming to the market as last-resort treatments. Yet current antibiotic surveillance systems are limited to monitor resistance to commonly prescribed drugs that have been on the market for a long time. This qualitative study determined the essential elements and requirements of antimicrobial resistance surveillance for new antibiotics based on literature review, interviews and expert consensus. After an extensive mapping exercise, ten experts participated in a modified Delphi consultation to identify consensus on all elements required for surveillance of resistance to novel antibiotics. The main findings indicate that there is a need for a 2-phase system; an early alert system transitioning to routine surveillance, led by the public sector to gather and share essential data on resistance to newer antibiotics in a transparent manner. The system should be decentralized, run largely from national level, but be coordinated by an arm of an existing international public health institution. Priority should be given to monitor emergence of resistance among already multi-drug resistant pathogens causing infections, over a broader selection of pathogens to maximize clinical impact. In conclusion, we cannot rely on current AMR surveillance systems to monitor resistance emergence to new antibiotics. A new, public system should be set-up, starting with a focus on detecting resistance emergence, but expanding to a more comprehensive surveillance as soon as there is regional spread of resistance to the new antibiotic. This article provides a framework based on expert agreement, which could guide future initiatives.